SAT0107 Efficacy and Safety After 64 Weeks of Ixekizumab Treatment in a Phase 2 Open Label Extension Study in Patients With Rheumatoid Arthritis. (23rd January 2014) - Genovese, M.; Carlier, H.; Erickson, J.; Braun, D.; Banerjee, S.
Abstract : Background: Ixekizumab, an anti-IL-17 mAb, has been evaluated in a Phase 2 study in patients (pts) with moderate or severe RA who were naïve to biologic therapy (bDMARD-naïve) or were inadequate responders to TNF inhibitors (TNF-IR). The primary 12 week endpoint was met, and significant improvements versus placebo (PB) were observed in both populations 1 . Objectives: To evaluate ixekizumab for long-term efficacy and safety in an open-label extension of the Phase 2 study. Methods: In this Phase 2 study, PB or ixekizumab was administered subcutaneously to 260 bDMARD-naïve pts (ixekizumab 3, 10, 30, 80, or 180 mg) and 188 TNF-IR pts (ixekizumab 80 or 180 mg) at Weeks 0, 1, 2, 4, 6, 8, and 10 with concomitant conventional DMARD therapy (Part A). After a treatment hiatus between Weeks 10 to 16, 232 bDMARD-naïve and 158 TNF-IR pts participated in the open-label extension, and all pts received ixekizumab 160 mg at Weeks 16, 18 and 20 and then every 4 weeks (Q4W) through Week 64 (Part B). Results: A total of 203 bDMARD-naïve (88%) and 106 TNF-IR (67%) pts completed the open label extension. Improvements in DAS28-CRP observed at Week 16 were maintained or improved after switching to 160 mg Q4W in Part B (Figure). For pts on PB in Part A, disease activity decreased in Part B to levels comparable with pts originally assigned to ixekizumab groups. DAS28<2.6 was achieved in 46 (23%) bDMARD-naive and 23 (22%) TNF-IR pts. Of pts with a good/moderate EULAR response at Week 16 (bDMARD-naïve n=145, TNF-IR n=78), this response was maintained through Week 64 (non-responder imputation) in 128 bDMARD-naïve (88%) and 52 TNF-IR (67%) pts. Similar maintenance of response was observed for ACR20, ACR50 and ACR70 in both populations. AEs occurred in 283 (73%) pts during Part B. Most AEs were mild to moderate in severity and did not lead to study discontinuation. Serious AEs were reported in 35 (9%) pts including 9 (2%) cases of serious infections. No mycobacterial or invasive fungal infections were reported. Image/graph: Conclusions: Clinical improvements observed with ixekizumab treatment in the double blind phase were maintained or improved in the pts that participated in the open label extension through Week 64. Ixekizumab was well tolerated, and there were no unexpected safety findings observed in Part B relative to Part A. References: Genovese et al. (2012) Ann Rheum Dis 71(Suppl3):59 Disclosure of Interest: M. Genovese Grant/research support from: Eli Lilly & Company, Consultant for: Eli Lilly & Company, H. Carlier Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, J. Erickson Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, D. Braun Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, S. Banerjee Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company